Papaya mealybug (Paracoccus marginatus) (Hemiptera: Pseudococcidae): A new threat to agri-horticulture ecosystem - LANEESHA M; SACHIN S SUROSHE; BABASAHEB B F; K SHANKARGANESH (The Indian Journal of Agricultural Sciences, 2020)
The papaya mealybug, Paracoccus marginatus Williams and Granara de Willink (Hemiptera: Coccomorpha: Pseudococcidae) is an invasive insect pest of Central American origin that has become a serious threat to about 60 plant species belonging to more than 22 families across the globe. The average life cycle of P. marginatus lasts between 15–32 days depending on host plant species and it can complete about 11–13 generations per year, depending on the temperature and relative humidity. It is of considerable economic importance and causes major losses to both agricultural and horticultural crops. In India, papaya mealybug became a major pest in 2009 with a devastating outbreak in south India. Even though several control methods, such as cultural, chemical, legal and biological control, have been adopted to tackle the problem, only chemical and biological control methods have been widely practised for its management. About 17 predators and 8 host specific parasitoids have been reported to give effective control of P. marginatus. However, the parasitoid Acerophagus papayae Noyes and Schauff (Hymenoptera: Encyrtidae) has played a predominant role in suppressing P. marginatus, with percentage parasitism in several countries between 75–81%. Owing to papaya mealybugs' polyphagy, wide climatic adaptability and ecological plasticity, it clearly has the potential to invade new areas and host plants and is likely to cause much damage in the future. In this paper, the origin, distribution, taxonomy, bio-ecology, host range, natural enemies, management practices and the possible effects of climate change on P. marginatus are critically reviewed. The information gathered will guide the management of this difficult to control insect pest.